2007
DOI: 10.2166/ws.2007.047
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of two estuaries to flooding and salinity intrusion

Abstract: This paper explores the vulnerability of two estuaries, the Clyde in Glasgow, Scotland, in the developed world with an established infrastructure, and where finance can be made available for adaption and mitigation. The other is in Gambia, West Africa, where poverty is endemic, the infrastructure undeveloped and where the finances for adaption and mitigation are severely limited. The paper employs a numerical modeling approach, first for the Clyde Estuary in Glasgow with a rich data-set modeled with commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Being fully analytical, an additional advantage is that it provides a comprehensive understanding of the entire salt intrusion process. Moreover, the reliability of this salt intrusion model has been extensively tested in a wide number of estuaries around the world, including the Maputo and Incomati (Savenije 1986), the Gambia (Savenije 1988, Risley et al 1993, Ervine et al 2007, the Chao Phya (Savenije 1989), the Yangtze (Zhang et al 2011), the Red River Delta (Nguyen et al 2012) and the Mekong (Nguyen andSavenije 2006, Nguyen et al 2008). Nguyen et al (2008) showed that this salt intrusion model can be utilized not only in a single river channel estuary but also in multiple branch delta estuaries.…”
Section: Introductionmentioning
confidence: 99%
“…Being fully analytical, an additional advantage is that it provides a comprehensive understanding of the entire salt intrusion process. Moreover, the reliability of this salt intrusion model has been extensively tested in a wide number of estuaries around the world, including the Maputo and Incomati (Savenije 1986), the Gambia (Savenije 1988, Risley et al 1993, Ervine et al 2007, the Chao Phya (Savenije 1989), the Yangtze (Zhang et al 2011), the Red River Delta (Nguyen et al 2012) and the Mekong (Nguyen andSavenije 2006, Nguyen et al 2008). Nguyen et al (2008) showed that this salt intrusion model can be utilized not only in a single river channel estuary but also in multiple branch delta estuaries.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been shown previously to be efficient (e.g. Brockway et al, 2006;Fang et al, 2006;Zhang et al, 2010). Table 2 shows the results of the fit for all these surveys carried out between 29 January to 3 February (the slope in column 4 and the dispersion coefficient in column 6).…”
Section: Model Calibrationmentioning
confidence: 94%
“…It has been validated well in numerous estuaries where the width converges exponentially (e.g. Savenije, 1989;Savenije and Pagès, 1992;Nguyen and Savenije, 2006;Eaton, 2007;Ervine et al, 2007;Nguyen et al, 2008). In the years 2000-2010, another analytical approach (Brockway et al, 2006) was put forward which can be considered to be a modified and simplified version of the method presented in earlier studies (Prandle, 1981;Savenije, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…This model assumed that alluvial estuaries could be simplified as ideal estuaries, with exponential reduction in width and cross-sectional areas. For two equilibrium conditions at high water slack (HWS) and low water slack (LWS), the resulting models have effectively predicted the intrusion length of saline water and the longitudinal salinity distributions in many estuaries worldwide (Eaton, 2007;Ervine, Bekic, and Glasson, 2007;Nguyen and Savenije, 2006;Savenije, 1988Savenije, , 1989Savenije and Pagès, 1992).…”
Section: Introductionmentioning
confidence: 99%